DECIMATED DREAMS? EDUCATION AND CAREER PROSPECTS AMONG STUDENTS UNDER TALIBAN GOVERNANCE - Yasini, Susan; Shamsi, Sayed Saied (Universitas Pendidikan Nasional, 2025)
This study explores the impact of Taliban-imposed educational restrictions on Afghan students, with a focus on Malika Suraya Girls' High School and Nasir Khisraw Boys' High School in Kabul. Afghanistan’s education system has long been shaped by conflict and instability, but the Taliban’s return to power in 2021 introduced unprecedented restrictions, particularly on female students. These restrictions have resulted in school closures, diminished access to formal learning, and constrained career prospects. While previous research has largely examined Afghanistan’s broader socio-political and economic context, few studies have quantitatively assessed the educational and career consequences of Taliban policies at the student level. This study employs a quantitative design, surveying 90 participants, including both students and teachers, to measure the effects of school closures on educational participation, adoption of informal learning, and shifts in career aspirations. Results indicate that female students were disproportionately affected by restrictions, with 77% of participants reporting changes in their career aspirations due to limited opportunities. The findings also show a notable rise in informal learning among female students as a coping strategy, while male students faced reduced motivation and career uncertainty. By using empirical evidence, this study contributes to debates on education in conflict and post-conflict societies, demonstrating how Taliban restrictions undermine human capital formation and long-term economic stability. The novelty lies in its quantitative approach, offering data-driven insights into how education policies under authoritarian regimes directly shape youth motivation, learning strategies, and professional trajectories.